(untitled) (The Agriculturists, 2010)
An experiment was conducted to study the effect of crop establishment methods and time of nitrogen application in Boro rice at the Bangladesh Rice Research Institute (BRRI) experimental farm, Gazipur during Boro season (2004-05). Five establishment methods viz; line sowing in zero tilled, broadcasting in zero tilled, line sowing in tilled, broadcasting in tilled wet soil and transplanting method and three times of nitrogen application viz; three splits of nitrogen application at 20, 40 and 85 DAS, four splits of nitrogen application at 20, 40, 60 and 85 DAS and leaf colour chart based nitrogen application methods were investigated. Line sowing in tilled wet soil gave the highest number of tiller m-2, panicles m-2, grains m-2, grain yield, straw yield, gross return, gross margin and less variable cost compared to other direct seeding and transplanting methods. In case of time of nitrogen application, four splits of nitrogen application gave the highest number of tiller m-2, panicles m-2, grains m-2, grain yield, straw yield, gross return, gross margin compared to other nitrogen application techniques.